(untitled) (CIPEEX, 2024)
SOLAR ENERGY HAS BEEN GAINING A LOT OF GROUND OVER THE YEARS, CURRENTLY REPRESENTING 13% OF THE BRAZILIAN ENERGY MATRIX AND SHOWING CONSISTENT GROWTH. HOWEVER, DESPITE THE PRESENTED DATA, SOME PARTS OF THE POPULATION EITHER LACK INTEREST OR SIMPLY DON’T HAVE THE NECESSARY AND CONCISE INFORMATION TO BETTER UNDERSTAND WHAT SOLAR ENERGY ENTAILS. WITH THIS IN MIND, WE BEGAN TO DEVELOP A PROJECT TO ADDRESS THIS NEED. TO DELVE INTO CREATING SOMETHING THAT MEETS THESE REQUIREMENTS, WE HAVE DEVELOPED A SYSTEM THAT, BASED ON DATA PROVIDED BY USERS, WILL PERFORM CALCULATIONS TO PROVIDE AVERAGE VALUES. THESE VALUES WILL SERVE AS A REFERENCE FOR USERS TO CLARIFY THEIR DOUBTS AND FORM THEIR OWN OPINIONS ABOUT SOLAR ENERGY PRODUCTS. THE SYSTEM NEEDS TO BE INFORMED OF THE MONTHLY ENERGY EXPENSES INCURRED BY THE USER. THIS WILL BE DONE AS FOLLOWS: A SOLAR PANEL COSTS BETWEEN 500 AND 1000 REAIS, DEPENDING ON THE TECHNOLOGY AND POWER OF THE EQUIPMENT. THIS COST VARIES BASED ON THE DOLLAR EXCHANGE RATE, MATERIALS USED IN MANUFACTURING, AND ITS EFFICIENCY. FOR A ROUGH IDEA, TO GENERATE AROUND 1000 KWH, APPROXIMATELY 22 SOLAR PANELS WOULD BE NEEDED. HOWEVER, THIS VALUE VARIES FROM PERSON TO PERSON AND FROM COMPANY TO COMPANY. IN THIS WAY, WITH THE ESTABLISHED VALUES AND USERS INFORMED ABOUT THEIR CONSUMPTION, THE APPLICATION WILL HAVE FULFILLED ITS PURPOSE. NEVERTHELESS, THIS ACHIEVEMENT WOULD BE SOMEWHAT SHALLOW COMPARED TO OUR INITIAL VISION. WE NEEDED SOMETHING THAT WOULD ENGAGE THE CUSTOMER AND EXPLORE THEIR DESIRES AND INTERESTS. THEREFORE, AFTER ESTABLISHING THE AVERAGE VALUES, THE CUSTOMER WILL HAVE FREE ACCESS TO THE SYSTEM, WITH A MENU OF COMPANIES AND A SECTION WITH VARIOUS DATA. THE COMPANIES’ SECTION AIMS TO PROVIDE ALL RELEVANT INFORMATION TO ESTABLISH A CUSTOMER-COMPANY RELATIONSHIP WHERE BOTH PARTIES BENEFIT. THE DATA SECTION SERVES TO ADD SOME TOPICS TO USERS. ONE OF THEM WOULD PROVIDE THE AVERAGE VALUES OF OTHER USERS AND THEIR OPINIONS ON THE SYSTEM’S PERFORMANCE OR THEIR RELATIONSHIP WITH THE OFFERED COMPANIES. USERS CAN ALSO SHARE THEIR OWN OPINIONS HERE. THIS SECTION WILL ALSO FOCUS ON ADDRESSING THE TOPIC OF SOLAR ENERGY AT ITS CORE, SHOWCASING ITS BENEFITS AND REASONS FOR INVESTMENT, INCLUDING VIDEOS AND RELIABLE SOURCES FOR DEEPER UNDERSTANDING. THIS IS A SUMMARY OF THE ESSENCE OF THE PROJECT, HOW IT WORKS, AND ITS OBJECTIVES. THIS IS A BASIC AND INITIAL IDEA, STILL ON PAPER, BUT AS THE PROJECT DEVELOPS, WE CAN MATURE IT OR PRESENT NEW SOLUTIONS TO CREATE WHAT WE WOULD CALL THE IDEAL PROJECT. &NBSP;